2007
DOI: 10.1016/s0928-2025(07)11126-3
|View full text |Cite
|
Sign up to set email alerts
|

9 Modelling river-bank-erosion processes and mass failure mechanisms: progress towards fully coupled simulations

Abstract: This paper reviews recent developments in modelling the two main sets of bankerosion processes and mechanisms, namely fluvial erosion and mass failure, before suggesting an avenue for research to make further progress in the future. Our review of mass failure mechanisms reveals that the traditional use of limit equilibrium methods to analyse bank stability has in recent years been supplemented by research that has made progress in understanding and modelling the role of positive and negative pore water pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 80 publications
(102 reference statements)
1
118
0
2
Order By: Relevance
“…Streambank recession rates were better correlated with maximum discharge than average discharge conditions, which would be expected in incised channels such as Walnut Creek where hydraulic erosion is considered the dominant bank erosion process (Thorne, 1982;Rinaldi and Darby, 2007). Hydraulic erosion removes bank materials from the direct erosive action of the flow (Darby et al, 2010).…”
Section: Recession Datamentioning
confidence: 95%
“…Streambank recession rates were better correlated with maximum discharge than average discharge conditions, which would be expected in incised channels such as Walnut Creek where hydraulic erosion is considered the dominant bank erosion process (Thorne, 1982;Rinaldi and Darby, 2007). Hydraulic erosion removes bank materials from the direct erosive action of the flow (Darby et al, 2010).…”
Section: Recession Datamentioning
confidence: 95%
“…Among the aforementioned sediment sources, riverbank erosion is considered a rather significant process in the context of fluvial dynamics as it involves a considerable fraction of the total sediment yield being supplied by riverbanks although its contribution varies between rivers [12][13][14][15]. Riverbank erosion may be caused by different phenomena, occurring with differing magnitudes and frequencies [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The riverbank characteristics of soil properties, length of rainfall periods, matric suction, geometry, and vegetation cover play important roles in bank failure and erosion-risk assessment [1,[26][27][28][29]. Millar [30] showed that bank vegetation also exerts significant control over alluvial channel patterns.…”
Section: Introductionmentioning
confidence: 99%